Body art/performing the subject - Jones, Amelia (Minneapolis : University of Minnesota Press, 1998)
Postmodernism, subjectivity, and body art : a trajectory -- The "Pollockian performative" and the revision of the modernist subject -- The body in action : Vito Acconci and the "coherent" male artistic subject -- The rhetoric of the pose : Hannah Wilke and the radical narcissism of feminist body art -- Dispersed subjects and the demise of the "individual" : 1990s bodies in/as art.
boek